2020
DOI: 10.1002/pds.5146
|View full text |Cite
|
Sign up to set email alerts
|

Validation of venous thromboembolism diagnoses in patients receiving rivaroxaban or warfarin in The Health Improvement Network

Abstract: PurposeTo describe the effect that validation of venous thromboembolism (VTE) coded entries in the health improvement network (THIN) has on incidence rates of VTE among a cohort of rivaroxaban/warfarin users.MethodsAmong 36 701 individuals with a first prescription for rivaroxaban/warfarin between 2012 and 2015, we performed a two‐step VTE case identification process followed by a two‐step case validation process involving manual review of patient records. A valid case required a coded entry for VTE at some po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Several general population studies have identified issues with relying solely on medical diagnoses including inaccuracy, missed events, and low PPV. 59,60 We found diagnoses misidentified potential VTEs when the documentation was referencing VTE prophylaxis not VTE. Diagnoses also were sometimes inaccurate in the setting of superficial phlebitis.…”
Section: Discussionmentioning
confidence: 98%
“…Several general population studies have identified issues with relying solely on medical diagnoses including inaccuracy, missed events, and low PPV. 59,60 We found diagnoses misidentified potential VTEs when the documentation was referencing VTE prophylaxis not VTE. Diagnoses also were sometimes inaccurate in the setting of superficial phlebitis.…”
Section: Discussionmentioning
confidence: 98%
“…The de nitions of outcomes were based on speci c diagnostic procedure codes (Read Codes in the UK, or International Statistical Classi cation of Diseases and Related Health Problems [ICD] 9th Revision or ICD 10th Revision in Germany, the Netherlands and Sweden) and were harmonized between databases as much as possible for the purpose of this analysis; studies that detail the design and validation of this methodology have previously been published [10,16]. The evaluated safety outcomes included bleeding events that led to hospitalization (as measure of severity), categorized as intracranial haemorrhage (intracerebral haemorrhage, subarachnoid haemorrhage or subdural haematoma), gastrointestinal bleeding (upper and lower gastrointestinal tract), urogenital bleeding and bleeding events at other sites [17]. All-cause mortality was also evaluated among rivaroxaban users.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of outcomes were based on specific diagnostic procedure codes (Read Codes in the UK, or International Statistical Classification of Diseases and Related Health Problems [ICD] 9th Revision or ICD 10th Revision in Germany, the Netherlands and Sweden) and were harmonized between databases as much as possible for the purpose of this analysis; studies that detail the design and validation of this methodology have previously been published [ 10 , 16 ]. The evaluated safety outcomes included bleeding events that led to hospitalization (as measure of severity), categorized as intracranial haemorrhage (intracerebral haemorrhage, subarachnoid haemorrhage or subdural haematoma), gastrointestinal bleeding (upper and lower gastrointestinal tract), urogenital bleeding and bleeding events at other sites [ 17 ]. All-cause mortality was also evaluated among rivaroxaban users.…”
Section: Methodsmentioning
confidence: 99%